1988
DOI: 10.1128/mcb.8.4.1756
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cell growth-regulating domains in the products of the adenovirus E1A oncogene.

Abstract: Among the various biological activities expressed by the products of the adenovirus EIA gene are the abilities to induce cellular DNA synthesis and proliferation in quiescent primary baby rat kidney cells. The functional sites for these activities lie principally within two regions of the ElA proteins: an N-terminal region and a small second region of approximately 20 amino acids further downstream. To study the biological functions of the first domain, we constructed an in-frame deletion of amino acid positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 65 publications
3
86
0
Order By: Relevance
“…This was surprising as CR2 has been implicated as having a possible role in cellular proliferation on the basis of its ability to associate with the retinoblastoma susceptibility gene product RB1 (11,63) and its necessity for immortalization (10,34,39,41,52,65). Certainly the loss of the RB1 gene or an inability to synthesize its product has been correlated with cellular proliferation (14,23,32,33) and in human cells infected or transformed by adenovirus or SV40, the complexing of RB1 by the viral transforming proteins is postulated to deprive the cell of a negative governor of cellular proliferation (8,36,63,64 (9) and which may have a similar role to the CR1 of ElA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was surprising as CR2 has been implicated as having a possible role in cellular proliferation on the basis of its ability to associate with the retinoblastoma susceptibility gene product RB1 (11,63) and its necessity for immortalization (10,34,39,41,52,65). Certainly the loss of the RB1 gene or an inability to synthesize its product has been correlated with cellular proliferation (14,23,32,33) and in human cells infected or transformed by adenovirus or SV40, the complexing of RB1 by the viral transforming proteins is postulated to deprive the cell of a negative governor of cellular proliferation (8,36,63,64 (9) and which may have a similar role to the CR1 of ElA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed it has been demonstrated that RB1 binding and transformation activity is maintained if the region homologous to CR2 of SV40 LT Ag replaces the CR2 of ElA (39). Thus these conserved regions are implicated in the transforming activity of the respective viral proteins (28,35,40,41,65).…”
mentioning
confidence: 99%
“…The amino terminus of E1A is required for induction of cellular DNA synthesis, enhancer repression, and transformation (for review, see Shenk and Flint 1991), but which of these activities is related to apoptosis remains to be determined. The PDdl mutation in E1A, however, can be distinguished from the other E 1A mutants examined because it produces a mutant protein that is completely defective for induction of cellular DNA synthesis (Moran and Zerler 1988;Stein et al 1991). The ability of E1A to release restrictions on growth control and induce S-phase, therefore, correlates with induction of apoptosis.…”
Section: Induction Of Proliferation By E1a May Be Incompatible With Rmentioning
confidence: 99%
“…fragment and inserted into pJ31q to yield an SV40-based expression construct. The pCMVneoBam vector was also used to express CD20 (Stamenkovic and Seed 1988) and E1A12S (Moran and Zerler 1988) cDNAs. Expression constructs for human cyclins A, B1, B2, and E were kindly provided by P. Hinds (Hinds et al 1992).…”
Section: Plasmid Constructsmentioning
confidence: 99%